Sorry, but it is impossible to solve this equation by itself. Since you have two unknowns, you need two equation.
Chat with our AI personalities
y = 2 (4X2=8) +9 = 17
4x2 - 4xy + y2 = (2x - y)2 so the length of the side of the square must be 2x-y.
It is (2x +y + 3)*(2x - y - 3).
y = 4x2 + 6 ory = 4x2 + 0x + 6, where a = 4, b = 0 and c = 6x-coordinate of the vertex = -b/2a = -0/2(4) = 0y-coordinate of the vertex = 4(02) + 6 = 6vertex is (0, 6)(Or you can say: Since the vertex of y = x is (0, 0), and this graph is shifted 6 units upward in the y-axis, then the vertex of y = x + 6 would be (0, 0 + 6) or (0, 6)Substitute 0 for y in order to find the roots.y = 4x2 + 60 = 4x2 + 60 - 6 = 4x2 + 6 - 6-6 = 4x2-6/4 = 4x2/4- 6/4 = x2± √(-6/4) = x± [√(6/4)]i = x x = [(1/2)√6]i or x = - [(1/2)√6]i
The question does not contain an equation: only an expression. An expression cannot have a vertex form.